HPV16 increases the number of migratory cancer stem cells and modulates their miRNA expression profile in oropharyngeal cancer. Issue 6 (7th May 2018) - Hufbauer, Martin; Maltseva, Margaret; Meinrath, Jeannine; Lechner, Axel; Beutner, Dirk; Huebbers, Christian U.; Akgül, Baki
Abstract : Human papillomavirus type 16 (HPV16) is a major risk for development of oropharyngeal squamous‐cell‐carcinoma (OPSCC). Although HPV + OPSCC metastasize faster than HPV − tumors, they have a better prognosis. The molecular and cellular alterations underlying this pathobiology of HPV + OPSCC remain elusive. In this study, we examined whether expression of HPV16‐E6E7 targets the number of migratory and stationary cancer stem cells (CSC). Furthermore, we wanted to elucidate if aberrantly expressed miRNAs in migratory CSC may be responsible for progression of OPSCCs and whether they may serve as potential novel biomarkers for increased potential of metastasis. Our studies revealed that HPV16‐E6E7 expression leads to an increase in the number of stationary (CD44 high /EpCAM high ) stem cells in primary keratinocyte cultures. Most importantly, expression of E6E7 in the cell line H357 increased the migratory (CD44 high /EpCAM low ) CSC pool. This increase in migratory CSCs could also be confirmed in HPV + OPSCC. Differentially expressed miRNAs from HPV16‐E6E7 positive CD44 high /EpCAM low CSCs were validated by RT‐qPCR and in situ hybridization on HPV16 + OPSCCs. These experiments led to the identification of miR‐3194‐5p, which is upregulated in primary HPV16 + OPSCC and matched metastasis. MiR‐1281 was also found to be highly expressed in HPV + and HPV − metastasis. As inhibition of this miRNA led to a markedly reduction of CD44 high /EpCAM low cells, it may prove to be a promising drug target. Taken together, our findings highlight the capability of HPV16 to modify the phenotype of infected stem cells and that miR‐1281 and miR3194‐5p may represent promising targets to block metastatic spread of OPSCC. Abstract : What's new? Human papillomavirus type 16 (HPV16) is a major risk factor for development of oropharyngeal squamous cell carcinoma (OPSCC). Interestingly, although HPV16 + OPSCC metastasize faster than HPV − tumors, they have a better prognosis. The molecular and cellular alterations underlying the pathobiology of HPV + OPSCC remain elusive, however. Here, the authors found that HPV16‐E6E7 oncogene expression can modify the phenotype of infected tissue stem cells, thereby increasing the number of migratory cancer stem cells. Additionally, miR‐1281 and miR‐3194‐5p were identified as potential biomarkers for migratory cancer stem cells and invasive HPV16 + OPSCC, thus representing promising targets for blocking metastatic spread of OPSCC.